Pertumbuhan Bibit Kakao (Theobroma cacao L.) Pada Berbagai Kombinasi Pupuk Anorganik NPK dan Pupuk Hayati Bioneensis di Polibag - Ramadhani, Rizky Fajriah; Hartawan, Rudi; Hayata, Hayata; Marwan, Edy (Jurnal Media Pertanian, 2024)
The cultivation of cocoa plants that began in nurseries, is an effort to increase cocoa production. High yields can be achieved with high-quality cocoa beans. This study aims to obtain a combination treatment of NPK inorganic fertilizer with the best Bioneensis bioorganic fertilizer to support the growth of cocoa seedlings. This study used a one-factor Complete Randomized Design. The treatment design tested was Bioneensis bioorganic fertilizer and NPK fertilizer with 5 levels of dosage and 3 replications. as follows:  b0 : Control, b1 : 7.5 g NPK fertilizer, b2 : 9.9 g Bioneensis fertilizer, b3 : 5 g NPK fertilizer (66.7% of b1) + 3.3 g of Bioneensis fertilizer (33.7% of b2), and b4: 2.5 g NPK fertilizer (33.7% of b1) + 6.6 g of Bioneensis fertilizer (66.7% of b2). and b4: 2.5 g NPK fertilizer (33.7% of b1) + 6.6 g of Bioneensis fertilizer (66.7% of b2). Implementation of research in the form of land preparation and shade,  preparation of planting media,  seedling preparation, feeding, treatment, and maintenance of plants. Plant height, stem diameter, header dry weight, root dry weight, root crown ratio, and quality index are the parameters that are measured. The results of this study concluded that treatment of 2.5 g of NPK fertilizer combined with 6.6 g of Bioneensis biofertilizer will increase plant height by 60.10%, rod diameter by 43.86%, The dry weight of the header was 183.31%, the dry weight of the roots was 229.41%, and the quality index was 189.20% compared to the control.